Effects of personalized invitation letters on research participation among general practitioners: a randomized trial - Hennrich, Patrick; Arnold, Christine; Wensing, Michel (BMC medical research methodology, 2021)
Participation of general practitioners is crucial for health care studies. However, recruiting them is an ongoing challenge and participation rates of general practitioners around the globe are often low. One feasible and cost-efficient approach to potentially enhance participation rates among general practitioners are personalized invitation letters, since they may increase one’s attention to and appreciation of a study. Still, evidence whether this method actually affects participation is scarce and ambiguous in relation to physicians.